Experimental Peri‐Implantitis around Different Types of Implants – A Clinical and Radiographic Study in Dogs. (26th February 2015) - Fickl, Stefan; Kebschull, Moritz; Calvo‐Guirado, José Luis; Hürzeler, Markus; Zuhr, Otto
Abstract: Background: The influence of the implant micro and macrostructure on peri‐implantitis is not fully understood. Purpose: To determine the effect of ligature‐induced peri‐implantitis on three commercially available implant types. Materials and Methods: Five beagle dogs were used. Two months following tooth extraction, three different implant types (BIOMET 3i T3, BIOMET 3i, Palm Beach Gardens, FL, USA; Straumann Bone Level, Straumann GmbH, Basel, Switzerland; Nobel Replace Tapered, Nobel Biocare, Gothenburg, Sweden) were placed in a randomized fashion in each hemi‐mandible. Peri‐implantitis was initiated by ligature placement and soft diet. Ligatures were added every 2 weeks for a total of four ligature advancements. After 2 weeks, the ligatures were removed, oral hygiene measures initiated for 3 weeks, and clinical (probing depth, mucosal recession, bleeding on probing), intrasurgical (intrasurgical defect depth, intrasurgical defect width), and radiographic (radiographic bone level) parameters assessed. Results: Nobel Replace Tapered implants showed significantly higher intrasurgical defect depth, intrasurgical defect width, probing depths, and radiographic bone level when compared to BIOMET 3i T3 or Straumann Bone Level implants. Straumann Bone Level implants showed largely similar clinical outcomes to BIOMET 3i T3. No significant differences between the groups were observed for mean mucosal recession. Conclusion: In an experimental peri‐implantitis model, Nobel Replace Tapered implants are associated with pronounced tissue loss.